Robust and durable poly(aryl-co-aryl piperidinium) reinforced membranes for alkaline membrane fuel cells. Issue 12 (23rd February 2022) - Hu, Chuan; Park, Jong Hyeong; Kim, Hae Min; Wang, Ho Hyun; Bae, Joon Yong; Liu, Mei-Ling; Kang, Na Yoon; Yoon, Kyoung-seok; Park, Chang-dae; Chen, Nanjun; Lee, Young Moo
Abstract : Polyethylene reinforced poly(aryl- co -aryl piperidinium) based membranes possess outstanding mechanical properties (tensile strength: 114 MPa, elongation at break: 159%) along with a fuel cell performance of 1.75 W cm −2 at 80 °C. Abstract : Robust and durable anion exchange membranes are crucial for cost-effective anion exchange membrane fuel cells (AEMFCs). Herein, we report high-performance poly(aryl- co -aryl piperidinium) (c-PAP) reinforced membranes with >95% visible light transmittance and a typical three-layer cross-sectional morphology for AEMFCs. Importantly, the reinforced composite membranes (RCMs) simultaneously possess ultrahigh tensile strength (TS, ∼114 MPa) and elongation at break (EB, ∼159%), which are improvements over the best-performing AEMs previously reported (mostly below 50 MPa of TS and 30% of EB). Additionally, the RCMs exhibit exceptional gas tightness (H2 crossover current density <0.2 mA cm −2 at 20% relative humidity (RH) and H2 permeability <10 Barrer), dimensional stability, and mechanical durability during RH cycling and pressure differential tests at 80 °C. Moreover, the RCMs maintain excellent mechanical and chemical durability after AEMFC testing at a current density of 0.6 A cm −2 at 70 °C for ∼360 h. The present RCM is an excellent candidate for alkaline energy device applications.